Helicobacter pylori genetic landscape in Northeast India and its impact in peptic ulcer disease and gastric cancer - Sarma, Anisha; Medhi, Devyashree; Sarma, Mridul Kumar; Saikia, Lahari; Choudhury, Bikash Narayan; Bhattacharya, Mallika; Sarma, Vaishali (Frontiers in Bacteriology, 2025)
IntroductionHelicobacter pylori (H. pylori), a globally prevalent bacterium is linked to various gastroduodenal diseases. Its genetic diversity arises from nucleotide variability, genome plasticity and inter-strain recombination. Genetic studies of H. pylori provide insights into human migration and regional disease risks. This study profiles the H. pylori gene pool in ethnically and geographically distinct population of Assam, Northeast India using multi-locus sequence typing (MLST) to explore its role in human migration and its potential role on the occurrence of gastroduodenal diseases in this region.MethodsIn this hospital-based study, gastric biopsy and serum samples were collected from 200 dyspeptic patients and H. pylori individual risk factors were assessed. Multivariate logistic regression was used to determine the statistical association between predictors and outcomes. Serum anti-H. pylori IgG levels were estimated and cagA and vacA virulence gene profiles were analysed by polymerase chain reaction. MLST analysis on the seven housekeeping genes and phylogenetic analysis were conducted to infer the genomic diversity and evolutionary relationship of the strains.ResultsH. pylori infection prevalence was 74.5% with significant associations between elevated serum IgG antibody levels, family history, virulent genotypes cagA, vacA s1m1 and gastric pathology, including cancer. MLST analysis identified 36 sequence types among 49 strains, including 8 new ones, with most strains clustering within the hpAsia2 and hpEurope populations. Phylogenetic analysis shows that H. pylori strains in the Assamese population cluster with native Thai strains, suggesting their introduction through Tai-Ahom migrants from Thailand, supporting gene flow into India. No clustering of gastric outcomes was observed among the strains. A strong familial link was noted, with 76.5% of gastric cancer cases having a family history, indicating possible intrafamilial transmission.DiscussionOur results suggest that H. pylori strains from Assam share ancestry with Tai-Ahom migrants from Thailand. Further, along with virulent genotypes, a family history of gastric cancer and high IgG levels may indicate higher disease risk. Future research should analyse strain transmission and IgG levels to improve early detection and intervention strategies for gastric cancer. IgG is a key predictor of gastric cancer risk, highlighting the importance of regular monitoring for early diagnosis and follow-up of high-risk individuals.